Egg production and quality of Magelang duck, Mojosari duck, and their reciprocal crosses - Henrik, Henrik; Marhayani, Marhayani (Faculty of Animal Science, Universitas Brawijaya, 2020)
This experiment was conducted to study the egg production and quality of Magelang, Mojosari duck, and their reciprocal crosses. Forty-eight of twenty weeks old ducks were used for a total of 4 treatments. The treatments were T1=Magelang duck; T2= ♂ Magelang x ♀ Mojosari; T3=Mojosari; and T4= ♂ Mojosari x ♀ Magelang. This research was design by Completed Randomized Design and replicated by 10 times according to number of female ducks in every treatment. Hen Day Production (HDP) as long as 12 weeks were collected as an egg production variable. Egg weight, albumen weight, yolk weight, shell thickness, and Haugh Unit (HU) as the egg quality variable. Data were analyzed by Analysis of Variance with one-way classification and Honestly Significance Difference. The result showed that were significantly different (P<0.01) on egg production and quality. The egg production was 60.57, 65.29, 68.86, and 61.00%, egg weight was 67.14, 59.79, 61.80, and 6.40 g, yolk weight was 25.06, 23.34, 23.23, and 24.46 g, albumen weight was 33.44, 31.41, 31.73, and 33.35 g, shell thickness were 0.50, 0.60, 0.57, and 0.53, HU were 74.24, 74.48, 72.57, and 71.03 respectively for T1, T2, T3, and T4. Egg production of Mojosari duck higher than Magelang duck (P<0.01) whereas egg quality of Magelang duck higher than Mojosari duck (P<0.01).